THE COMPARATIVE STUDY BETWEEN JIGSAW TECHNIQUE AND STUDENTS TEAM ACHIEVEMENT DIVISION TO IMPROVE STUDENTS’ READING SKILL AT EIGHT GRADE OF SMP N 4 TOLITOLI - Ma'rifa A Saleng (Jurnal Madako Education, 2020)
The objective of the research was to compare the effectiveness jigsaw and STAD at the eight  grade   of   SMPN 4   Tolitoli. It was true experimental research. It was conducted at the eight grade of   SMPN 4 Tolitoli. The researcher gave a pre-test to measure the students previous reading skill. Then, a post test was to find out the students reading skill after giving treatment which used jigsaw technique and STAD. The researcher used SPSS 21 program to analyze the data collection. The result of the data analysis showed that the average score of VIII C (Jigsaw class) was for the 51,472 pre- test and 81,904 for the post-test. The average score of VIII A (STAD class) was 53,412 for the pre-test and 80,364 for the post-test. Jigsaw technique and STAD was effective to improve students’ reading skill at the eight grade of SMPN 4 Tolitoli. Although, both of the  technique  could  improve  students’  reading  skill  but  the  obtained  score  of  t-test showed that t-score -0,646 was lower than t-table 2,011. It meant that Ho was accepted and Ha was rejected. Since, the tc was lower than tt, there was no significance difference in the achievement students in class VIII C who were tought mind Jigsaw technique and students in class VIII A who were taught STAD. Key words: Comparative, Jigsaw technique, STAD, Reading skill